Report on the international scientific conference the Real Library – Library Reality, organised by the Institute of Library and Information Science of Eötvös Loránd University, Budapest, November 28–29, 2023 - Németh, Katalin (Folia Toruniensia, 2024)
Since 2013, the Institute of Library and Information Science of Eötvös Loránd University in Budapest, Hungary has been organising the largest library and information science event, called the Real Library – Library Reality Conference, in Hungary every two years. In 2023, the two–day, peer-reviewed international conference with more than 50 speakers, focused on libraries and the market economy. On the first day of the conference, library and archive directors, economists, and academics shed light on the economic and political environment of the cultural sector. On the second day, the institute's lecturers and doctoral students presented their research, and there was also an English-language session with the Sukhothai Thammathirat Open University (Thailand) and Oslo Metropolitan University (Norway).